Inhibitory potential of phytochemicals on five SARS-CoV-2 proteins: in silico evaluation of endemic plants of Bosnia and Herzegovina - Tarik Corbo; Abdurahim Kalajdzic; Dzenita Omerkic; Farah Catic; Naris Pojskic; Kasim Bajrovic (Biotechnology & Biotechnological Equipment, 2023)
The outbreak of the coronavirus disease 2019, caused by the SARS-CoV-2 virus, has prompted global health concerns. In response, researchers have been conducting investigations on active compounds in plants that may hold the potential to inhibit the proliferation of the virus. The aim of this study was to simulate and predict structural interactions of selected compounds isolated from 28 endemic plants of Bosnia and Herzegovina against the main protease (Mpro), papain-like protease (PLpro), RNA-dependent RNA polymerase (RdRp), spike glycoprotein and uridylate-specific endoribonuclease (NendoU) of SARS-CoV-2. The majority of compounds, especially hesperidin, showed great binding affinity to the target proteins. The highest affinity for Mpro was observed for genistein and hesperidin, while in terms of structural interactions, both compounds achieved interactions of interest. Hesperidin and luteolin were the compounds with the highest binding affinity for PLpro, but no significant interactions were observed. For RdRp, hesperidin and quercetin showed the highest binding affinity, where both compounds formed interactions of interest. Hesperidin and fisetin were the compounds with the highest binding affinity for spike glycoprotein, and both compounds achieved significant interactions. The highest affinity for NendoU was obtained for hesperidin and isorhamnetin, where both compounds formed interactions of interest. Although these findings appear encouraging, further research is needed, which includes in vitro and in vivo assessments, along with clinical trials, to provide evidence for the potential therapeutic uses of these plants.